2018
DOI: 10.1093/ijnp/pyy069
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Treatment Response in Depression: The Role of Anterior Cingulate Cortex

Abstract: BackgroundIdentification of biomarkers predicting therapeutic outcome of antidepressant treatment is one of the most important tasks in current research because it may transform the lengthy process of finding the right treatment for a given individual with depression. In the current study, we explored the potential of pretreatment pregenual anterior cingulate cortex activity as a putative biomarker of treatment response.MethodsThirty-two medication-free patients with depression were treated for 6 weeks with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 38 publications
3
50
2
Order By: Relevance
“…Beata and others (Godlewska et al, 2018) have also shown that pretreatment pgACC activity is predictive of response to escitalopram after 6 weeks. FC of subcallosal cingulate cortex could identify individuals' treatment outcome to cognitive behavioral therapy (CBT) and antidepressant medicine .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Beata and others (Godlewska et al, 2018) have also shown that pretreatment pgACC activity is predictive of response to escitalopram after 6 weeks. FC of subcallosal cingulate cortex could identify individuals' treatment outcome to cognitive behavioral therapy (CBT) and antidepressant medicine .…”
Section: Introductionmentioning
confidence: 84%
“…This potentially suggested that lower DMN related connectivity is a feasible predictor of effective antidepressant medications (Ma et al, ). Beata and others (Godlewska et al, ) have also shown that pretreatment pgACC activity is predictive of response to escitalopram after 6 weeks. FC of subcallosal cingulate cortex could identify individuals' treatment outcome to cognitive behavioral therapy (CBT) and antidepressant medicine (Dunlop et al, ).…”
Section: Introductionmentioning
confidence: 85%
“…In order to address the question of why only some people respond to medications, pre-treatment differences in brain function and structure between future responders and non-responders, as well as correlations between baseline brain activity and a change in depression severity over treatment, were explored (e.g. [7,8,9,10]). These studies have provided valuable information on the mechanisms of action of AD treatments and the factors that determine response to individual drugs [11].…”
Section: Single Drug Studiesmentioning
confidence: 99%
“…At this point, probably the best supported candidate for a neuroimaging response biomarker is pgACC, with its increased activity being a predictor of good clinical response consistently shown over the past 20 years (e.g. [10,22,23]) and supported by meta-analyses and systematic reviews [19, 20••]. PgACC plays a crucial role in the development of depressive symptoms and antidepressant response due to its central position between the circuits responsible for a quick automatic response to emotionally salient stimuli and prefrontal regions exerting cognitive control over them.…”
Section: Pregenual Anterior Cingulate Cortex (Pgacc): a General Respomentioning
confidence: 99%
“…Separately, an important potential opportunity in the clinical management of depression is predicting treatment response. 20 Only 50% of individuals respond to the first treatment they are offered, 21 and lengthy trial-and-error approaches incur significant patient and health-service costs. Digital phenotyping using voice analysis 22 provides a proof of concept for new methods to predict treatment response but improvements in prediction accuracy are now needed to enable clinical uses.…”
Section: Introductionmentioning
confidence: 99%